Rupture of the Distal Biceps Tendon Combined with a Supinator Muscle Tear in a 51-Year-Old Woman: A Case Report - Samir Nayyar; Martin Quirno; Saqib Hasan; Leon Rybak; Robert J. Meislin (Case Reports in Radiology)
Distal biceps tendon rupture is a relatively uncommon occurrence in the general female population, and to our knowledge, has not been reported in association with a supinator muscle tear. We report a case of 51-year-old woman who experienced sharp pain in her forearm and elbow after lifting a heavy object. History and physical examination raised suspicion for a distal biceps tendon rupture. MRI imaging determined a combined distal biceps tendon tear with a supinator muscle tear with subsequent confirmation at surgery. Surgical repair was performed for the distal biceps tendon only through a single incision approach using the Endobutton technique.